The Relationship Between Auditory and Cognitive Processing Abilities in Children With Specific Learning Disorders. - Jain, Saransh; Kothari, Siddharth; V. S., Rohith; H. S., Harshan Kumar; Jain, Chandni (American Journal of Audiology, 2024)
Purpose: Specific learning disorder (SLD) refers to a pattern of learning difficulties characterized by problems with reading, writing, or mathematics that are not solely due to intellectual disabilities, sensory deficits, or other neurological or medical conditions. It is a neurodevelopmental disorder that affects the processing and organizing of information. Auditory and cognitive processing is affected in most children with SLD, although to a varying degree. However, it is still unclear whether there exists any relationship between auditory and cognitive processing disorders in children with SLD. Method: We tested 1,259 children, of whom 77 were diagnosed as SLD and 30 age- and gender-matched typically developing (TD) children were selected. Auditory processing abilities were assessed for auditory discrimination, pattern perception, closure, temporal processing, binaural integration, and separation using standardized tests and procedures. Cognitive processing was measured using working memory, short-term memory, and attention tasks. Results: The test data of the TD children were taken as the norm. Based on the normative range, children with SLD were divided into those with auditory processing disorder (APD; n = 31) and those without APD (n = 46). A regression model highlighted a robust positive relationship between APD and cognitive processing, particularly pronounced in SLD with APD children. The results are discussed, supporting the information-processing theory of learning disability and highlighting a complex loop between auditory and cognitive deficits in children with SLD. Conclusions: The findings underscore the critical role of both auditory and cognitive abilities in children with SLD. Tailoring the intervention to break the loop is recommended, which may improve learning abilities more effectively.